Impact of climate resilient technologies in rainfed agro-ecosystem - K, JASNA V; BURMAN, R R; PADARIA, R N; SHARMA, J P; VARGHESE, ELDHO; CHAKRABARTI, BIDISHA; DIXIT, SREENATH (The Indian Journal of Agricultural Sciences, 2017)
Climate change has been given the dubious moniker for asymmetrical development of Indian economy in general and agriculture sector in particular. Climate resilient technologies are promising tool to guard a farming system from climatic variations. National Initiative on Climate Resilient Agriculture (NICRA) has demonstrated, and promoted application of climate resilient technologies in most vulnerable 100 districts. This study has been conducted to recognize the technological and socio-economic impact of these technologies upon the society. To enable impact assessment the study employed with –without and before-after comparison, of samples of two NICRA and two non-NICRA villages constituting 120 respondents. Among the technologies demonstrated in the NICRA villages, improved soil and land management practices, water management practices, crop production interventions and cropping system interventions were compared. Various analyses demonstrated that significant difference between NICRA and non-NICRA, farmers on cropping intensity, crop diversification, average irrigated land area and irrigation frequency, employment generation, land area (leased in) and annual savings, with a favorable tilt towards NICRA group. Before-after comparison of NICRA group, to isolate the project impact also testified significant improvement on a set of indicators like average irrigated land area and irrigation frequency, employment generation, land area (leased in), savings, crop yield and expenditure pattern. The study thus provides a springboard for the policy makers and civil societies to stretch out the activities for wide adaptation.